Yield response of tef (Eragrostis tef) to nitrogen, phosphorus, potassium and sulphur under balanced fertilization on Vertisols in different agroecological zones of Ethiopia - Chala, Girma; Kassa, Sofia; Tadele, Tsadik; Assefa, Kefyalew; Teshome, Habtemariam; Agegnehu, Getachew; Abera, Wuletawu; Tibebe, Degife; Sileshi, Gudeta W.; Erkossa, Teklu (Cambridge University Press, 2022)
Nutrient deficiency is a major constraint in tef (Eragrostis tef (Zucc.) Trotter) production in Ethiopia. In the past, a blanket recommendation of nitrogen (N) and phosphorus (P) fertilizers has been applied regardless of the diversity of agroecological zones and soil types. As crop responses declined with widespread deficiencies of nutrients, farmers have lost interest in applying the recommended fertilizer rates. The present study was conducted with the objective of quantifying the response of tef to different rates of N, P, potassium (K) and sulphur (S) fertilizers under balanced application of the nutrients other than the one under investigation. In each region, the same set of trials was implemented on farmers’ fields for three years. All trials were implemented on Vertisols across four agroecological zones (AEZs). The treatments were seven rates of N, six rates each of P and S and eight rates of K with a basal application of zinc (Zn) and boron (B). The results showed that the most limiting nutrient is N followed by P in each agroecological zone on the Vertisols. There was clear evidence of increases in grain yield with increasing rates of N and P, but the responses to K and S rates did not follow clear trends across AEZs. With balanced application of the other nutrients, 23–92 kg N ha−1 increased grain yield by 11–92%, while 10–40 kg P ha−1 increased yields by 12–33% over the control in the different AEZs. Based on results from dose–response models, it is concluded that the agronomic optimum rates for tef production are 69 kg N, 20 kg P, 30 kg K and 10 kg S ha−1 in the cool sub-moist mid-highlands and the tepid sub-humid mid highlands; 92 kg N, 30 kg P, 15 kg K and 10 kg S ha−1 in tepid moist mid highlands but 69 kg N, 10 kg P, 15 kg K and 10 kg S ha−1 in the tepid sub-moist mid highlands. On Vertisols not covered by this study, these recommendations should be subject to appropriate soil and plant analysis. We also recommend further studies on the nutrient requirement of tef on other soil types and AEZs.